TINDAK TUTUR ILOKUSI BAHASA IKLAN PRODUK PADA MEDIA SOSIAL INSTAGRAM SHIREEN SUNGKAR - Asnaini, Asnaini; Sari, Ayu Puspita Indah (Jurnal Ilmiah Bina Bahasa, 2023)
Abstract: This research aims to describe how the illocutionary speech acts of advertising language on Shireen Sungkar's Instagram social media. This research is a type of qualitative research using Rusminto's theory (2009). The data collected in this study used observation techniques and recording techniques. The source of the data is from Shireen Sungkar's Instagram social media in the form of videos in Shireen Sungkar's Instagram channel. The data of this research uses speech in Shireen Sungkar's instagram advertisements taken in the video of Shireen Sungkar's instagram social media. The analysis techniques used by researchers in this study are (1) transcribing existing data (2) classifying data (3) grouping according to forms of speech acts (4) analyzing data (5) concluding research results. Based on the data and discussion, the researcher obtained and found that the advertising speech in Shireen Sungkar's Instagram video used illocutionary speech acts as much as 6 data. The illocutionary speech acts found are assertive, directive, commissive, and expressive consisting of 1 assertive illocutionary speech act, 3 directive illocutionary speech acts, 1 commissive illocutionary speech act, and 1 expressive speech act. The illocutionary speech acts of advertising language on Shireen Sungkar's Instagram social media products become a medium in promoting product results to be very effective. Keywords: Speech, Illocutionary Acts of Speech, Instagram Shireen Sungkar.